LEARNING MATHEMATICS IN TELUKDALAM MARKET: CALCULATING PRICES AND MONEY IN LOCAL TRADE - Gaurifa, Midarwati; Darmawan Harefa (Universitas Nias Raya, 2024)
This study aims to develop a contextual mathematics learning method using the market as a learning medium in Telukdalam. The main focus of the research is to enhance students' abilities in calculating prices and money within local trade. Through this approach, students not only learn basic mathematical concepts but also relate them to real-life situations they encounter in their daily lives. A literature review method is employed to examine relevant literature on contextual mathematics learning and the importance of social interaction in the learning process. The results indicate that learning experiences in the market can enhance students' motivation and understanding of mathematical material. Additionally, this learning approach enriches local social and cultural values, leading students to appreciate their environment and traditions more. It is hoped that the findings of this study will contribute to the development of a more relevant and contextual mathematics curriculum.